Current Vaccination Practice in Diabetic (Diabetes I) Patients - Kumar, Yati; Sundaram, Sonali; Yadav, Deepika (Current Diabetes Reviews, 2024)
The worldwide prevalence of diabetes, an endocrine condition, is rising quickly. The alarming rise of diabetes in recent years has emerged as a major contributor to premature death and illness among persons of working age. The potential use of immunomodulatory drugs to prevent diabetes has been a source of worry in light of recent advances in our understanding of the role of autoimmune responses in the development of diabetes. Vaccines can work in a variety of ways, including by eliminating autoreactive T-cells or by blocking the connections between immune cells. Most diabetes vaccines that have been created so far have only been evaluated in animal models, with just a small number having undergone successful human trials. In this article, the authors also look at the clinical trial research that are currently being conducted to create a prototype diabetes vaccine.
Keywords: diabetes